Thinking Outside the Box: Exploring Indonesian EFL Pre-Service Teachers’ Conceptions and Perceptions of Creativity - Rahman, Kasyfur; Rahmat, Hery (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2025)
The aim of this study is to explore how EFL pre-service teachers conceptualize and perceive creativity. A total of 226 pre-service teachers enrolled at a state university, Universitas Islam Negeri Mataram, participated in a survey, and six of them voluntarily took part in a follow-up focus group interview. Their conceptions of creativity were investigated using open-ended questions and interviews. In addition, their perceived creativity was assessed through a self-report scale adapted from the Creativity Styles Questionnaire–Revised (CSQ-R). The findings indicate that their conceptions are partially aligned with prevailing theories of creativity, encompassing creative outcomes, individual traits, and creative processes. Furthermore, the majority of participants identified themselves as medio-creative. Creative individuals reported greater use of techniques, heightened sensory awareness, control over environmental and behavioral factors, and stronger beliefs in unconscious processes. The study also discusses implications for pre-service teacher education. Abstrak: Tujuan dari penelitian ini adalah untuk mengeksplorasi bagaimana calon guru bahasa inggris memahami dan memandang kreativitas. Dua ratus dua puluh enam calon guru yang sedang menjalani studi di Universitas Islam negeri Mataram berpartisipasi dalam sebuah survei tentang kreativitas, dan enam di antaranya secara sukarela berpartisipasi dalam wawancara kelompok terfokus. Data tentang konsepsi kreativitas mereka dikumpulkan menggunakan pertanyaan open-ended dan wawancara. Data persepsi kreativitas diperoleh melalui respons calon guru terhadap skala yang diadaptasi dari Creativity Styles Questionnaire-revised (CSQ-R). Hasil penelitian menunjukkan bahwa konsepsi calon guru tentang kreativitas sejalan dengan sebagian besar teori kreativitas. Mereka memahami kreativitas sebagai hasil kerja kreatif, ciri-ciri pribadi, dan proses kreatif. Selain itu, sebagian besar responden mengidentifikasi diri sebagai medio-kreatif. Individu yang kreatif mengungkapkan penggunaan teknik, indera, dan kontrol lingkungan/perilaku yang lebih tinggi serta kepercayaan pada proses bawah sadar. Implikasi untuk pendidikan calon guru juga disajikan. The aim of this study is to explore how EFL pre-service teachers conceptualize and perceive creativity. A total of 226 pre-service teachers enrolled at a state university, Universitas Islam Negeri Mataram, participated in a survey, and six of them voluntarily took part in a follow-up focus group interview. Their conceptions of creativity were investigated using open-ended questions and interviews. In addition, their perceived creativity was assessed through a self-report scale adapted from the Creativity Styles Questionnaire–Revised (CSQ-R). The findings indicate that their conceptions are partially aligned with prevailing theories of creativity, encompassing creative outcomes, individual traits, and creative processes. Furthermore, the majority of participants identified themselves as medio-creative. Creative individuals reported greater use of techniques, heightened sensory awareness, control over environmental and behavioral factors, and stronger beliefs in unconscious processes. The study also discusses implications for pre-service teacher education. Abstrak: Tujuan dari penelitian ini adalah untuk mengeksplorasi bagaimana calon guru bahasa inggris memahami dan memandang kreativitas. Dua ratus dua puluh enam calon guru yang sedang menjalani studi di Universitas Islam negeri Mataram berpartisipasi dalam sebuah survei tentang kreativitas, dan enam di antaranya secara sukarela berpartisipasi dalam wawancara kelompok terfokus. Data tentang konsepsi kreativitas mereka dikumpulkan menggunakan pertanyaan open-ended dan wawancara. Data persepsi kreativitas diperoleh melalui respons calon guru terhadap skala yang diadaptasi dari Creativity Styles Questionnaire-revised (CSQ-R). Hasil penelitian menunjukkan bahwa konsepsi calon guru tentang kreativitas sejalan dengan sebagian besar teori kreativitas. Mereka memahami kreativitas sebagai hasil kerja kreatif, ciri-ciri pribadi, dan proses kreatif. Selain itu, sebagian besar responden mengidentifikasi diri sebagai medio-kreatif. Individu yang kreatif mengungkapkan penggunaan teknik, indera, dan kontrol lingkungan/perilaku yang lebih tinggi serta kepercayaan pada proses bawah sadar. Implikasi untuk pendidikan calon guru juga disajikan.